(untitled) (SciELO Preprints, 2022)
In the framework of the study of Siluriform fish monogeneans of Lake Tanganyika, we described two new species of Bagrobdella from Auchenoglanis occidentalis, Bagrobdella vanhovei sp. nov. is characterized by the morphology of its MCO which is unique (terminal opening) and Bagrobdella vansteenbergei sp. nov. characterized by the size of its hooks, which are almost all of the same size, and its male copulating organ with a unique shape: sub-terminal opening and no membrane surrounding.